2022
DOI: 10.33963/kp.a2022.0094
|View full text |Cite
|
Sign up to set email alerts
|

Recording an isoelectric interval as an endpoint of left bundle branch pacing with continuous paced intracardiac electrogram monitoring

Abstract: Background:The present study aimed to evaluate the feasibility and safety of the novel left bundle branch pacing (LBBP) procedure that uses isoelectric interval as an endpoint for lead implantation.Methods: A total of 41 patients with indications for pacing were enrolled. All patients underwent a novel LBBP procedure guided by recording an isoelectric interval as an endpoint for lead implantation. The procedural details and electrophysiological characteristics were then analyzed.Results: A total of 38/41 (92.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…During the screwring procedure, the tail of pacing lead was always connected with the John Jiang's connecting cable. The recent research by our team has showed that the equipment might be more effective and convenient to monitor ECG, EGM, and impedance in real time to avoid perforation and to guide effective endpoint without the need to stop pacing (Shen, Jiang, Cai, et al, 2022; Shen, Jiang, Jiang, et al, 2022; Wu et al, 2022), so when the vascular pathway was established, TVA angiography was performed, and sheath was placed in what we thought the ideal position, the screwing of lead started. During the process, a narrow premature beat which shows right bundle branch conduction delay (RBBD) with an rSR pattern in V1 occurred (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the screwring procedure, the tail of pacing lead was always connected with the John Jiang's connecting cable. The recent research by our team has showed that the equipment might be more effective and convenient to monitor ECG, EGM, and impedance in real time to avoid perforation and to guide effective endpoint without the need to stop pacing (Shen, Jiang, Cai, et al, 2022; Shen, Jiang, Jiang, et al, 2022; Wu et al, 2022), so when the vascular pathway was established, TVA angiography was performed, and sheath was placed in what we thought the ideal position, the screwing of lead started. During the process, a narrow premature beat which shows right bundle branch conduction delay (RBBD) with an rSR pattern in V1 occurred (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…At this time, the lead screwing was stopped and the impedance was monitored frequently Immediately, an isoelectric interval on the ECG and an S‐V interval on the EGM were recorded (Figure 2). In our recent study, we proposed a novel LBBP procedure that used isoelectric interval as an endpoint for lead implantation (Wu et al, 2022), so, based on our experience, the LBB was captured and the whole process lasted about 57 s and was successful at one time.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective observational study enrolled consecutive patients who underwent successful permanent pacemaker implantation. LBBP uses John Jiang's connecting cable (Xinwell Medical Technology Co., Ltd., Ningbo, Zhejiang, China) for the continuous pacing and recording technique, and the procedure has been described by us elsewhere (7)(8)(9)(10). The study protocol was approved by the Ethics Committee of the Hwa Mei Hospital, Ningbo, China.…”
Section: Patient Population and Definition Of Lbb Capturementioning
confidence: 99%
“…LBBP uses the continuous pacing and recording technique, and the procedure has been described by us in detail elsewhere. [8][9][10] The study protocol was approved by the Ethics Committee of the Hwa Mei Hospital, Ningbo, China. Written informed consent was obtained from all patients.…”
Section: Patient Population and Definition Of Lbb Capturementioning
confidence: 99%